IMPLEMENTATION OF ISLAMIC SPIRITUAL ACTIVITIES USING THE TAHSIN AND TAJWID METHODS TO SUPPORT THE PERSONALITY DEVELOPMENT OF INMATES AT THE PALU CLASS IIA CORRECTIONAL FACILITY - L, Ramadhan; Soge, Markus Marselinus (Universitas Nusa Cendana, 2026)
This study examines the implementation of Islamic spiritual development through tahsin and tajwid methods in supporting the personality development of inmates at the Class IIA Correctional Facility in Palu. Correctional institutions are not only responsible for enforcing sentences but also for preparing inmates for successful reintegration into society through character and moral development. Using a qualitative descriptive approach, data were collected from primary and secondary sources through observation, interviews, and document analysis. The study is guided by implementation theory and the concept of correctional development (SPPN). The findings show that tahsin and tajwid activities contribute positively to shaping inmates’ discipline, religious awareness, and moral character. These programs also encourage collaboration with external parties, strengthening the overall development process within the institution. However, the implementation of the program still faces several challenges, including weak religious foundations among inmates, limited budget and human resources, low intrinsic motivation, and environmental factors that are not fully supportive. In conclusion, although the tahsin and tajwid approach has demonstrated positive outcomes, improvements in resources, program support, and motivational strategies are necessary to enhance its effectiveness in fostering inmates’ personality development and supporting their social reintegration. Keywords: Corrections; Islamic Spirituality; Tahsin; Tajwid; Inmate Rehabilitation